Development of a non-linear PCI model for homogeneous zones of concrete airport pavements. Issue 6 (21st December 2020) - Kwak, Pyung-Jin; Kim, Dong-Hyuk; Kim, Seung-Jae; Jeong, Jin-Hoon
Abstract : The pavement condition index (PCI) is a tool for evaluating pavement performance and is based on the type and severity of surface distress. It is used to determine maintenance times, methods and location priorities. Most previous PCI prediction models have considered only pavement age or traffic volume as a variable, without consideration of other factors that affect pavement distress. In this study, data from 12 airports were analysed using reports published from 1994 to 2013. The airport pavements were divided into homogeneous zones according to their function and structure. For improved management of concrete airport pavements, a non-linear PCI model was developed for the homogeneous zones and tornado diagrams were used to analyse the sensitivity of the PCI according to the independent variables of the model. The results showed that the developed model can predict the PCI of homogeneous zones of concrete airport pavements more reasonably by considering various factors that affect pavement distress.